(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article covers interesting information and skills on the most effective reading, listening and speaking skills that will facilitate the learning of foreign languages. This article aims to further increase the number of people who know foreign languages and increase their interest in the language. These tips will be useful for those who are new to learning a foreign language and for those who want to strengthen their knowladge.